2011
DOI: 10.1080/10508406.2010.508029
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Children to Learn Effectively: Exploring the Value of Intrinsic Integration in Educational Games

Abstract: The concept of intrinsic motivation has been considered to lie at the heart of the user engagement created by digital games. Yet despite this, educational software has traditionally attempted to harness games as extrinsic motivation by using them as a sugar-coating for learning content. This paper tests the concept of intrinsic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
251
3
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 464 publications
(306 citation statements)
references
References 51 publications
6
251
3
10
Order By: Relevance
“…Based on the findings of ElHilly and colleagues [57], it is intrinsic motivation that may function as a positive drive to engagement in a prevention program and to a positive health behavior as well, while external social influences might rather have a negative impact on the overall efficacy of gamification. Similar results were published by Habgood and Ainsworth [58], indicating that in-game intrinsic motivators are more effective than extrinsic ones in case of educational games.…”
Section: Discussionsupporting
confidence: 87%
“…Based on the findings of ElHilly and colleagues [57], it is intrinsic motivation that may function as a positive drive to engagement in a prevention program and to a positive health behavior as well, while external social influences might rather have a negative impact on the overall efficacy of gamification. Similar results were published by Habgood and Ainsworth [58], indicating that in-game intrinsic motivators are more effective than extrinsic ones in case of educational games.…”
Section: Discussionsupporting
confidence: 87%
“…This aspect of CAR builds upon the principle of conceptual integration (Cheng 2011;Clark et al 2011;Habgood and Ainsworth 2011;Kafai 1996). Proponents of conceptual integration claim that the mode of interaction activates and refines in the child the same set of conceptual resources that would be activated when reasoning about some target real-world phenomenon (Fig.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…This is possible because in a conceptually integrated design, the way the player interacts with the game IS the concept of interest (Clark et al 2011;Habgood and Ainsworth 2011). Habgood and Ainsworth (2011) created Zombie Division, a game designed to teach young children fractions, to illustrate and evaluate the value of a conceptually integrated design (they use the term intrinsic integration). In Zombie Division the various modes of attack available to the player embody the fractions of interest.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…This leaves the question of how to integrate these in an effective manner unanswered. In an experiment comparing intrinsic embedding of the learning content with the gameplay to an extrinsic embedding, Habgood et al found an increased motivation for the activities [92]. The integration of learning with gameplay, and hence the alignment of gameplay activities with learning activities, is a topic of ongoing research.…”
Section: Integration and Alignmentmentioning
confidence: 99%